A Uropathogenicity Island Contributes to the Pathogenicity of Escherichia coli Strains That Cause Neonatal Meningitis - Houdouin, Véronique (American Society for Microbiology, 2002)
We report that the archetypal Escherichia coli strain C5 causing neonatal meningitis harbors a pathogenicity island (PAI) designated PAI I(C5) that is similar to the PAI II(J96) of uropathogenic E. coli J96 inserted in the leuX-tRNA gene. PAI-negative C5 mutants had a lower capacity than C5 to induce high-level bacteremia in a neonatal rat model. However, no change in their resistance to the bactericidal effect of serum and their capacity to cross the blood-brain barrier was observed.